Enriching the intersection of service and transformative learning with Freirean ideas: The case of a critical experiential learning programme in Brazil. Issue 5 (November 2020) - Dal Magro, Rosane; Pozzebon, Marlei; Schutel, Soraia
In this article, we examine the value of combining transformative and service learning pedagogical practices in management education programmes to encourage management students to be more critical and reflexive regarding serious contemporary issues like social inequality and sustainability. We draw on a long-term management education experience conducted in the northeastern region of Brazil, where international students learn how to develop a real-time community-based project with local inhabitants. We argue that while service learning approaches promote pragmatic action-based principles, transformative learning acts at the epistemic level, contributing to change in values. In addition, Paulo Freire's ideas are integrated to reinforce critical and reflexive dimensions of the learning experience. Our results offer a process-based model showing how a critical experiential learning pedagogy might lead to the development of community-based competences, which, in turn, might lead to changes in the deeply held values of the participants. Freire's emancipatory ideas are applied not only regarding the relationship between teachers and students, but also to the distinction between Western and non-Western societies, going beyond questioning of the destructive consequences of financial capitalism to question the hegemony of one worldview over all other possible ones.